Production-sharing in East Asia: implications for India - Rajan, Ramkishen S. (2003)
Despite beginning the industrialisation process ahead of most of east Asia, India's manufactured exports as a whole have stagnated when benchmarked against east Asia. While its east Asian neighbours have been able to move rapidly from manufactured labour-intensive commodities. India has largely been left out of the production-sharing process. If India is to become a manufacturing powerhouse like china and most of the other middle-income countries in east Asia, it needs to take steps to integrate more effectively and intensively with the rest of east Asia and become an important participant in the regional and global division of labour. - Reproduced.
Keywords: Manufacturing industries